Driving Along the Road or Heading for the Village? Conceptual Differences Underlying Motion Event Encoding in French, German, and French–German L2 Users. Issue 1 (February 2015) - Flecken, Monique; Carroll, Mary; Weimar, Katja; Von Stutterheim, Christiane; Bylund, Emanuel; Athanasopoulos, Panos
ABSTRACT The typological contrast between verb‐ and satellite‐framed languages (Talmy, 1985) has set the basis for many empirical studies on L2 acquisition. The current analysis goes beyond this typology by looking in detail at the conceptualization of the path of motion in a motion event. We take as a starting point the cognitive salience of specific elements of motion events that are relevant when conceptualizing space. When expressing direction in French, specific spatial relations involving the entity in motion (its alignment and its distance toward a [potential] endpoint) are relevant, given a variety of path verbs in the lexicon expressing this information (e.g., se diriger vers, avancer 'to direct oneself toward, ' 'to advance'). This is not the case in German (manner verbs in the lexicon mainly). In German, spatial information is packaged in adjuncts and particles and the path of motion is typically structured via features of the ground (entlanglaufen/fahren 'to walk/drive along') or endpoints ('to walk/drive to/toward'). We investigate those fundamental differences in spatial conceptualization in French and German, as reflected in pre‐articulatory patterns of attention allocation (measured with eye tracking) to moving entities and endpoints in motion scenes in an event description task. Our focus is on spatial conceptualization in an L2 (French L2 users of German), analyzing the extent to which these L2 users display target‐like patterns or traces of L1 conceptualization transfer. Findings show that, in line with directional concepts expressed in verbs, L1 French speakers allocate more attention to entities in motion and endpoints, before utterance onset, than L1 German speakers do. The L2 German speakers pattern with L1 German speakers in the use of manner verbs, but they have not fully acquired the spatial concepts and means that structure the path of motion in the L2. This is reflected in pre‐articulatory attention allocation patterns, according to which the L2 speakers pattern with native speakers of their L1 (French). The findings show a continued deep entrenchment of L1‐based processing patterns and spatial frames of reference when speakers prepare for speech in an L2.